Exposure of feral swine to Coxiella burnetii overlaps with human Q fever incidence in California - McMillan, Ian A.; Golon, Samuel J.; Norris, Michael H.; Franckowiak, Gregory A.; Grinolds, James M.; Bowen, Richard A.; Brown, Vienna R.; Borlee, Bradley R. (Frontiers in Epidemiology, 2026)
Coxiella burnetii is a zoonotic pathogen that causes Q fever in humans. There are many known reservoirs of C. burnetii, including cattle, sheep, and goats with an expanding list of potential reservoirs including birds, reptiles, ticks and additional mammalian species, such as swine. Feral swine are a highly invasive species in the United States with significant populations and a broad geographic distribution. The role of feral swine in the transmission and spread of C. burnetii is poorly understood, although a recent report identified overlap between feral swine seroprevalence and human Q fever incidence in Texas. California accounts for a large proportion of human Q fever cases in the United States and in this study we characterized the seroprevalence of C. burnetii in feral swine populations in the state. Feral swine showed seropositivity rates up to 1.64% indicating some level of exposure and the possibility that they may serve as a reservoir for disease transmission and spread. Overlap with human Q fever incidence was identified in the central region of California. Although this study does not directly link feral swine to human infection, it identified spatial overlap between feral swine seroprevalence and human Q fever incidence in the state of California, possibly due to the presence of ruminants as the principal reservoirs of C. burnetii. The environmental stability and low infectious dose of C. burnetii, coupled with the geographic overlap between feral swine seroprevalence and human Q fever incidence suggests that feral swine may contribute to zoonotic disease transmission and spread.